Team management by a modern manager: from models to practice (Economics and region, 2025)
The article analyses the evolution of approaches to organizing teamwork in management activities, considering contemporary challenges that necessitate a rethinking of the role of the manager in the context of digitalization. Based on the disclosure of classical models (Tuckman, Belbin, Drexler-Sibbet), a systematic approach to team formation and development is proposed. This made it possible to reveal teamwork as a modern management technology, which, in conditions of high uncertainty and limited time, allows making management decisions and ensuring the stability of organizations. It has been proven that effective team functioning in the modern organizational environment is possibly provided that: taking into account the stages of team interaction development (time is needed for its creation and the efforts of the leader), distribution of roles according to R. Belbin (identification of strengths and weaknesses), and definition of clear tasks for the team (for its creation and functioning).
Keywords: team; teamwork; model; digital competencies; manager